Utility Privatization and the Needs of the Poor in Latin America : Have We Learned Enough to Get It Right? - Estache, Antonio; Gomez-Lobo, Andres; Leipziger, Danny (World Bank, Washington, DC, 2014)
Efforts to reform utilities can affect poor households in varied, often complex, ways, but it is by no means certain that such reform will hurt vulnerable households. Many myths have been perpetuated in discussions of utility reform - and in many cases poor households have benefited from reform. What is amazing is the extent to which governments, and their advisors - sometimes including multilateral organizations - fail to measure, anticipate, and monitor how the privatization of utilities actually affects the poor. Many questions must still be answered before good general guidelines can be drawn, but the authors offer many suggestions about how social, regulatory, and privatization policy, can increase the benefits of utility reform for poor households. The good news is that many measures can be taken to improve the chances that poor households will benefit from reform. Chief among these is promoting competition, where possible. Essentially what is needed is political commitment to doing the right thing. If policy is weak before privatization, it is going to be weak after privatization as well. Privatization is no substitute for responsible policy on redistribution.